Valoración de la hostilidad en escolares que usan videojuegos - Liza Vasquez, Luis Eduardo (2015)
To determinate hostility on students of Max Ludwig Planck high school who play videogames Materials and Methods: There were included 154 students, between 11 and 17 years old, who studied at Max Ludwig Planck high school in Trujillo. Everyone took the Aggression Questionnaire from Buss and Perry, which was modified and has 29 items, every answer was evaluated and grouped in four classes physical aggression, verbal aggression, rage and hostility; also a quiz that ask about the frequency and how did the students describe the games that they play. We used MS – Excel to process the data and stage the results. Results: The 66% of the students get at least one component of aggressive behavior according to the AQ test. The most prevalent characteristic in the group was the hostility in 43% of the students. A relationship between the practice of videogames and physical aggression, anger and hostility is evident. Conclusions: We concluded that there is a relationship between aggressive behavior, like physical aggression, anger, hostility and the practice of videogames